Identification of metastable lattice distortion free charge density wave at photoinduced interface via TRARPES - Shaofeng Duan; Binshuo Zhang; Zihao Wang; Shichong Wang; Lingxiao Gu; Haoran Liu; Jiongyu Huang; Jianzhe Liu; Dong Qian; Yanfeng Guo; Wentao Zhang (npj Quantum Materials)
Abstract The interplay between different degrees of freedom governs the emergence of correlated electronic states in quantum materials, with charge density waves (CDW) often coexisting with other exotic phases. Under thermal equilibrium, traditional CDW states are consequentially accompanied by structural phase transitions. In contrast, ultrafast photoexcitation allows access to exotic states where a single degree of freedom dominates in the time domain, enabling the study of underlying physics without interference. Here, we report the realization of a long-lived metastable CDW state without lattice distortion at the photoinduced interfaces in GdTe3 using time- and angle-resolved photoemission spectroscopy. After optical excitation above the CDW melting threshold, we identified emerged metastable interfaces through inverting the CDW-coupled lattice distortions, with lifetimes on the order of 10 picoseconds. These photoinduced interfaces represent a novel CDW state lacking the usual amplitude mode and lattice distortions, allowing quantification of the dominant role of electronic instabilities in CDW order. This work provides a new approach to disentangling electronic instabilities from electron-phonon coupling using a nonequilibrium method.